"I would have lost the respect of my friends and family if they knew I had bent the road rules": Parents, peers, and the perilous behaviour of young drivers. (January 2015) - Scott-Parker, B.; Watson, B.; King, M.J.; Hyde, M.K.
Highlights: Parents thought to hold non-risky attitudes; not always good models who are imitated. Reactions of parents/friends depends on outcome of risky behaviour (crash, no crash). Males report risky friends, who are also unlikely to sanction risky driving. 'Making a trip more exciting for mates' important factor in riskiness of young men. Abstract: Young novice drivers are at considerable risk of injury on the road. Their behaviour appears vulnerable to the social influence of their parents and friends. The nature and mechanisms of parent and peer influence on young novice driver (16–25 years) behaviour was explored via small group interviews ( n  = 21) and two surveys ( n1  = 1170, n2 =  390) to inform more effective young driver countermeasures. Parental and peer influence occurred in pre-Licence, Learner, and Provisional (intermediate) periods. Pre-Licence and unsupervised Learner drivers reported their parents were less likely to punish risky driving (e.g., speeding). These drivers were more likely to imitate their parents and reported their parents were also risky drivers. Young novice drivers who experienced or expected social punishments from peers, including 'being told off' for risky driving, reported less riskiness. Conversely drivers who experienced or expected social rewards such as being 'cheered on' by friends – who were also more risky drivers – reported more risky driving including crashes and offences. Interventions enhancing positive influence and curtailing negative influence may improve road safety outcomes not only for young novice drivers, but for all persons who share the road with them. Parent-specific interventions warrant further development and evaluation including: modelling safe driving behaviour by parents; active monitoring of driving during novice licensure; and sharing the family vehicle during the intermediate phase. Peer-targeted interventions including modelling of safe driving behaviour and attitudes; minimisation of social reinforcement and promotion of social sanctions for risky driving also need further development and evaluation.